Chasing newsroom diversity : from Jim Crow to affirmative action - Mellinger, Gwyneth (Urbana : University of Illinois Press, 2013)
Social change triggered by the Civil Rights Movement in the 1960s sent the American Society of Newspaper Editors (ASNE) on a fifty-year mission to dismantle an exclusionary professional standard that envisioned the ideal journalist as white, straight, and male. In this book, the author explores the complex history of the decades-long ASNE diversity initiative, which culminated in the failed Goal 2000 effort to match newsroom demographics with those of the U.S. population. Explaining why a project so promising failed so profoundly, this book expands our understanding of the intransigence of institutional racism, gender discrimination, and homophobia within democracy. -- Publisher's description.
Introduction : the black and white of newspapers -- Manning the barricade : maintaining the white prerogative in the face of change, 1954-1967 -- Seeking justice in a climate of irony : the hiring initiative's uneasy prelude, 1968-1976 -- "A sensitive and difficult task" : establishing a framework for newsroom integration, 1977-1989 -- The gay Nineties : reimagining and renegotiating a multicultural newsroom -- Diversity in crisis : ASNE's time of reckoning, 1998-2002 -- Afterword : closing a chapter of newspaper history.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Minority journalists -- United States; African Americans in the newspaper industry; Minorities in journalism -- United States; American newspapers -- History -- 20th century; Diversity in the workplace -- United States; Minorities -- Employment -- United States; Journalistes issus des minorités -- États-Unis.; Noirs américains dans les entreprises de presse; Minorités en journalisme -- États-Unis.; Journaux américains -- Histoire -- 20e siècle.; Multiculturalisme en milieu de travail -- États-Unis.; Minorités -- Travail -- États-Unis.; LANGUAGE ARTS & DISCIPLINES -- Journalism; POLITICAL SCIENCE -- Civil Rights; African Americans in the newspaper industry; American newspapers; Diversity in the workplace; Minorities -- Employment; Minorities in journalism; Minority journalists; United States; 1900-1999; History